Rubber composite material and preparation method thereof

By using ionic liquid copolymerization sulfur in rubber composite materials to catalyze the silanization reaction of white carbon black and silane coupling agent, the problem of reducing the modulus and fracture strength of rubber composite materials in the prior art is solved, and a significant improvement in high static mechanical properties and dynamic fatigue properties are achieved.

CN119859331AActive Publication Date: 2025-04-22SOUTH CHINA UNIV OF TECH +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510077748.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-22
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

In the prior art, when the rubber performance is improved by catalyzing the silanization reaction of white carbon black in situ catalyzing the ionic liquid, the ionic liquid has poor compatibility with the rubber, resulting in a decrease in the modulus and fracture strength of the rubber composite material, and failure due to ionic liquid migration during processing and storage.

Method used

Rubber composite materials including raw rubber, white carbon black, ionic liquid copolymerization sulfur, silane coupling agent, anti-aging agent and vulcanization package are used to catalyze the silanization reaction of white carbon black and silane coupling agent in situ through ionic liquid copolymerization sulfur, thereby improving the dispersion degree of white carbon black in the rubber matrix and the interaction between rubber and white carbon black.

Benefits of technology

The quasi-static mechanical properties and dynamic fatigue properties of rubber composites have been significantly improved, the tensile strength increases by about 30%, the 300% fixed-extension stress increases by about 33%, the loss factor decreases by about 35%, and the fatigue temperature increase decreases by about 51%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a rubber composite material and a preparation method thereof. The rubber composite material comprises the following raw materials: raw rubber, white carbon black, ionic liquid copolymerized sulfur, a silane coupling agent, an anti-aging agent and a vulcanization bag, the weight of the white carbon black is 50wt%-100wt% of that of the raw rubber, the weight of the ionic liquid copolymerized sulfur is 0.1 wt%-3wt% of that of the white carbon black, and the ratio of the weight of the silane coupling agent to the weight of the white carbon black is less than or equal to 10wt%. The rubber composite material can fully utilize the ionic liquid copolymerized sulfur to catalyze the silanization reaction of the white carbon black in situ, so that the dispersion of the white carbon black in a rubber matrix is improved, the interface action of rubber and the white carbon black is enhanced, and the rubber composite material has high quasi-static mechanical property and dynamic fatigue property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tread rubber, and in particular relates to a rubber composite material and a preparation method thereof. Background Art

[0002] Rubber composites filled with silica are known as "green tire" tread materials, which can balance rolling resistance and anti-skid properties. However, due to the presence of a large number of silanol groups on the surface of silica, silica tends to aggregate in the rubber matrix, thus affecting the performance of the rubber composite. Therefore, the uniform dispersion of silica in the rubber matrix and the strong interface between rubber and silica are the key to obtaining a rubber composite with excellent comprehensive performance.

[0003] In order to give full play to the application potential of white carbon black in rubber composite materials, especially in tires, researchers have used a variety of surface treatment technologies to improve the compatibility of white carbon black with rubber, such as physical coating or covalent grafting of white carbon black with coupling agents or polymers, and treating white carbon black with electron beams or plasma. Patent application document CN106832417B discloses a method of modifying white carbon black with aliphatic polyoxyethylene ether by chemical bonding and physical adsorption to achieve the purpose of good dispersion of white carbon black in the rubber matrix. Patent application document CN110734653B discloses a method of modifying white carbon black by chemical coating and controlling the surface chemical properties of white carbon black by controlling the type and content of silane coupling agent. The above methods usually have the defects of insufficient interaction between white carbon black and rubber matrix interface and the need to add additional steps of pre-modifying white carbon black. In order to further improve the interaction between silica and rubber, patent application document CN104804231A discloses a method for improving the dynamic properties of tread rubber by using small molecule ionic liquid to catalyze the silanization reaction between silica and silane coupling agent. However, the tread rubber modified by the above method has low modulus and breaking strength, and often fails due to the migration of ionic liquid during processing and storage.

[0004] In the process of realizing the present invention, the inventors found that there are at least the following problems in the prior art: in the process of improving the performance of rubber by in-situ catalyzing the silanization reaction of white carbon black with ionic liquid, due to the large difference in polarity between the small molecules of ionic liquid and non-polar rubber and poor compatibility with rubber, the ionic liquid will play a plasticizing role and reduce the modulus and fracture strength of the rubber composite material; and during processing and storage, the ionic liquid will migrate from the inside of the rubber to the surface and become ineffective. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a rubber composite material and a preparation method thereof in view of the above-mentioned deficiencies of the prior art, in which white carbon black is uniformly dispersed in a rubber matrix and has high static mechanical properties and dynamic fatigue properties.

[0006] In order to solve the above technical problems, on the one hand, a rubber composite material is provided, wherein the raw materials include raw rubber, white carbon black, ionic liquid copolymer sulfur, silane coupling agent, antioxidant and vulcanization package, the weight of white carbon black is 50wt% to 100wt% of the raw rubber, the weight of the ionic liquid copolymer sulfur is 0.1wt% to 3wt% of the white carbon black, and the weight of the silane coupling agent / the weight of the white carbon black is ≤10wt%.

[0007] Compared with the prior art, the present invention has the following advantages:

[0008] 1. The present invention provides a rubber composite material having significantly improved quasi-static mechanical properties, significantly reduced rolling resistance and significantly improved anti-skid performance, wherein the tensile strength is increased by up to about 30%, the 300% elongation stress is increased by up to about 33%, the loss factor is reduced by about 35%, and the fatigue temperature rise is reduced by about 51%.

[0009] 2. The rubber composite material of the present invention comprises raw rubber, white carbon black, ionic liquid copolymerized sulfur and silane coupling agent as raw materials. The sulfur chains in the ionic liquid copolymerized sulfur are grafted with the rubber molecular chains, the compatibility of the rubber and the ionic liquid is increased, the catalytic efficiency of the silanization reaction of the silane coupling agent and white carbon black is improved, the dispersion degree of white carbon black in the rubber matrix is ​​improved, and the interface interaction between white carbon black and rubber is significantly enhanced.

[0010] 3. In the rubber composite material of the present invention, the amount of silane coupling agent used can be as low as 4wt% of the mass of white carbon black, so as to obtain a rubber composite material with high quasi-static mechanical properties and dynamic fatigue properties.

[0011] 4. In the rubber composite material of the present invention, the comprehensive performance of the rubber composite material is strongly related to the alkalinity of the ionic liquid copolymer sulfur, and the modification effect can be regulated by changing the composition of the ionic liquid copolymer sulfur.

[0012] 5. The method of preparing the rubber composite material of the present invention only requires in-situ addition of ionic liquid copolymer sulfur during the preparation process of the rubber composite material to achieve the preparation of the rubber composite material without requiring any extra steps, which is conducive to promotion and application in industry.

[0013] The technical solution of the present invention is further described in detail below in conjunction with embodiments. DETAILED DESCRIPTION

[0014] The technical solution of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0015] In the following description, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural.

[0016] In the following description, the terms "include", "comprising", "having" and "containing" are open-ended terms, meaning including but not limited to.

[0017] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0018] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be understood as each intermediate value between the upper and lower limits of the scope also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.

[0019] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0020] The technical principle adopted by the present invention is as follows: the ionic liquid copolymer sulfur comprises an ionic liquid part and a sulfur chain part, the ionic liquid part can have multiple interactions with the silicon hydroxyl groups on the surface of white carbon black to generate silicon oxygen anions, catalyze the silane coupling agent and white carbon black to undergo a silylation reaction, the polysulfide bonds can be broken under high temperature conditions to generate sulfur free radicals, the ionic liquid part is grafted onto the rubber molecular chain, the compatibility of the ionic liquid and the rubber is improved, and the catalytic efficiency of the silylation reaction is improved, the ionic liquid part and the sulfur chain part in the ionic liquid copolymer sulfur cooperate with each other and play a role as a whole, so as to achieve a high dispersion of white carbon black in the rubber matrix, the interface interaction between rubber and white carbon black is stronger, the hysteresis loss is lower, and higher quasi-static mechanical properties and dynamic fatigue properties are shown.

[0021] Some embodiments provide a rubber composite material: the raw materials include raw rubber, white carbon black, ionic liquid copolymerized sulfur, silane coupling agent, antioxidant and vulcanization package; the weight of white carbon black is 50wt% to 100wt% of the raw rubber, the weight of ionic liquid copolymerized sulfur is 0.1wt% to 3wt% of the white carbon black, and the weight of silane coupling agent / weight of white carbon black is ≤10wt%. The ionic liquid copolymerized sulfur is used to in-situ catalyze the silanization of white carbon black, improve the dispersion characteristics of white carbon black in the rubber matrix, enhance the interface interaction between rubber and white carbon black, and obtain a rubber composite material with high static mechanical properties and dynamic fatigue properties. The weight of the ionic liquid copolymerized sulfur is 0.1wt% to 3wt% of the white carbon black. The inventors found that when the weight of the ionic liquid copolymerized sulfur is limited to 0.1wt% to 3wt% of the white carbon black, the silanization reaction of the catalytic silane coupling agent and the white carbon black can be simultaneously enhanced, and the direct interface strength between the rubber and the white carbon black can be enhanced by the polysulfide chain. The use efficiency of the silane coupling agent and the dispersion of the white carbon black in the rubber matrix are significantly improved. When the amount of the ionic liquid copolymerized sulfur is less than 0.1wt% of the white carbon black, the catalytic effect on the silanization reaction between the silane coupling agent and the white carbon black is weak, and the performance of the rubber composite material cannot be well optimized. When the amount is higher than 3wt% of the white carbon black, the hysteresis loss of the rubber composite material is significantly increased and the dynamic performance is reduced. This may be due to the strong polarity of the ionic liquid copolymerized sulfur.

[0022] Ionic liquid copolymer sulfur is a type of copolymer sulfur, which is prepared by the free radical addition reaction of sulfur radicals generated by sulfur in a thermally excited state with monomers containing olefin groups. Its synthesis methods mainly include the following two methods: one is that under high temperature conditions, sulfur and ionic liquids containing olefin groups are subjected to bulk polymerization to directly obtain ionic liquid copolymer sulfur; the other is that when the ionic liquid is an ionic liquid containing amine compounds such as imidazole and halogen groups, under high temperature conditions, sulfur is firstly copolymerized with olefins containing halogen groups through free radical addition, and then amine compounds such as imidazole are added to carry out quaternization reaction to obtain ionic liquid copolymer sulfur.

[0023] In some embodiments, the structure of the ionic liquid copolymer is shown as follows:

[0024]

[0025] Where x is 2-6; R 1 It is a fatty chain molecule or an aromatic ring molecule, wherein the fatty chain molecule includes a hydrocarbon fatty chain molecule and / or a fatty chain molecule containing a heteroatom, wherein the fatty chain molecule includes a linear fatty chain molecule and / or a branched fatty chain molecule; and the heteroatom includes O and / or N;

[0026] R 2 The ionic liquid part includes a cation part and an anion part, wherein the cation part is alkyl imidazole, alkyl pyridine or organic phosphorus salt, and the anion part is chloride, bromide, iodine, hexafluorophosphate, tetrafluoroborate, acetate or hydroxide.

[0027] In some embodiments, in the ionic liquid part, the cationic part is alkyl imidazole, and the anionic part is hydroxide, acetate or chloride, and more preferably, the anionic part is hydroxide; in the ionic liquid copolymer sulfur, the alkalinity of the cation is from large to small: alkyl imidazole, alkyl pyridine, organic phosphorus salt; the alkalinity of the anion is from large to small: hydroxide, acetate, chloride, bromine, iodine, hexafluorophosphate, tetrafluoroborate. The inventors found that the alkalinity of the ionic liquid copolymer sulfur affects the performance of the rubber composite material, which is manifested as the stronger the alkalinity of the ionic liquid copolymer sulfur, the higher the comprehensive performance of the rubber composite material, and its modulus and rolling resistance performance are significantly improved. This may be because the stronger the alkalinity of the ionic liquid copolymer sulfur, the stronger the promotion effect on the silanization reaction between the silane coupling agent and the white carbon black.

[0028] In some embodiments, the weight of the silane coupling agent is 4wt% to 10wt% of the white carbon black, and the silane coupling agent is an alkoxysilane containing a functional group. Further preferably, the silane coupling agent is a sulfur-containing alkoxysilane. In some specific embodiments, the silane coupling agent is a silane coupling agent Si69 or Si75. Adding a sulfur-containing silane coupling agent, such as bis-[γ-(triethoxysilyl)propyl]tetrasulfide (Si69) and / or bis-[3-(triethoxysilyl)propyl]-disulfide (Si75), can achieve in-situ modification of the rubber composite material, which is mainly due to the presence of two different functional groups in the silane coupling agent, namely, an alkoxy group and a sulfur-containing organic functional group. The alkoxy group undergoes a condensation reaction with the silicon hydroxyl group on the surface of the white carbon black, and the sulfur-containing organic functional group reacts with the rubber to couple the rubber with the white carbon black. The reaction activity of silane coupling agent and white carbon black is low, and a large amount of silane coupling agent needs to be added to improve the modification effect. Usually, the amount of silane coupling agent added is about 10wt% of the mass of white carbon black. The inventor found that the added silane coupling agent does not improve the modification effect in the same direction, but will generate multiple molecular layers on the surface of white carbon black due to self-condensation or intermolecular condensation, forming an uncontrollable interface structure. The inventor unexpectedly found that in the rubber composite material containing the above-mentioned ionic liquid copolymer sulfur and sulfur-containing silane coupling agent, the condensation reaction of alkoxy and silicon hydroxyl on the surface of white carbon black can occur while coupling with the rubber molecule on the basis of low silane coupling agent addition (the minimum amount of silane coupling agent addition can be 4wt% of the weight of white carbon black), so as to achieve efficient and rapid silanization reaction, and the use efficiency of silane coupling agent is higher. At the same time, it was found that the generation of environmentally harmful products such as alcohol VOC during the reaction process was significantly reduced.

[0029] In some embodiments, the raw rubber is diene rubber. The inventors have found that under high temperature conditions, a large number of sulfur free radicals generated by ionic liquid copolymerization sulfur will add to double bonds in diene rubber and / or capture allylic hydrogen protons, couple rubber molecular chains and graft, so that ionic liquid copolymerization sulfur-modified white carbon black specifically modifies diene rubber and improves the comprehensive performance of rubber.

[0030] In some preferred embodiments, the raw rubber is one or more of styrene-butadiene rubber, natural rubber and butadiene rubber; in some specific embodiments, the raw rubber is solution-polymerized styrene-butadiene rubber, solution-polymerized styrene-butadiene rubber and butadiene rubber in a mass ratio of 7:3, or solution-polymerized styrene-butadiene rubber and natural rubber in a mass ratio of 7:3.

[0031] In some specific embodiments, the antioxidant is antioxidant 4010NA, and the vulcanization package includes zinc oxide, stearic acid, accelerator CZ and accelerator D, and sulfur. The antioxidant is a common raw material in the rubber industry, and the amount and type of the antioxidant vary depending on the type of raw rubber; the vulcanization package is a common raw material in the rubber industry, and the type of the vulcanization package varies depending on the type of raw rubber.

[0032] In another aspect, a method for preparing a rubber composite material is provided, comprising:

[0033] S1. The first mixing stage: add raw rubber, antioxidant, white carbon black, silane coupling agent and ionic liquid copolymer sulfur into an internal mixer in sequence, with a rotor speed of 20-40 rpm, mix for 3-10 minutes, discharge the rubber at 50-70°C to obtain a mixed rubber; when the mixing time is less than 3 minutes, the raw rubber, white carbon black and other auxiliary components cannot be evenly mixed. When the mixing time is more than 10 minutes, the mechanical properties of the rubber compound decrease significantly. This may be due to the serious chain breakage of the rubber molecular chain caused by the longer mixing time.

[0034] S2. Second stage mixing: the first stage of the mixed rubber is allowed to stand and cool at room temperature, the cooled first stage of the mixed rubber is placed in an internal mixer for mixing, the rotor speed is 30-70 rpm, the mixing is performed for 2-6 minutes, the discharge temperature is 130-170°C, and a second stage of the mixed rubber is obtained, the second stage of the mixed rubber is allowed to stand and cool at room temperature; when the second stage mixing time is less than 2 minutes, the performance of the rubber composite material is poor, which may be due to the low mixing time, the promotion effect of the silanization reaction is not significant, and the promotion efficiency is low. When the mixing time exceeds 6 minutes, the rubber material is heated at high temperature for a long time, and defects such as scorching and oxidation fracture that directly affect the performance of the rubber composite material may occur.

[0035] S3. Add the cooled second-stage mixed rubber to the open mill, make a triangular package, unroll the sheet, leave it overnight, and vulcanize it to obtain a rubber composite material. The method for preparing the rubber composite material has a high degree of compatibility with the traditional rubber mixing process, and only needs to add ionic liquid copolymerization sulfur in situ to achieve rubber modification, without the need for extra steps or special equipment.

[0036] The present invention has been subjected to a series of experiments before the application is filed. A part of the experimental results are listed here to further describe the invention in detail, and the following is a detailed description in conjunction with the embodiments.

[0037] Example 1

[0038] According to the formula in Table 1, raw rubber, antioxidant, white carbon black, silane coupling agent and ionic liquid copolymer sulfur are added to an internal mixer in sequence for first-stage mixing for 5 minutes, and the rotation speed is controlled to discharge the rubber at 60°C to obtain a rubber mix; the rubber mix is ​​then allowed to cool at room temperature, and the cooled rubber is placed in an internal mixer for second-stage mixing for 6 minutes, and the rotation speed is controlled to discharge the rubber at 130°C. After cooling, a vulcanization bag is added to the open mixer, and the sheet is removed after triangle bagging, and then allowed to stand overnight, and compression-vulcanized at 150°C according to the positive vulcanization time to obtain a sample. The corresponding formulas and samples are shown in Comparative Sample 1, Sample 1, Sample 2 and Sample 3.

[0039] According to the formula in Table 1, raw rubber, antioxidant, white carbon black, silane coupling agent and ionic liquid copolymer sulfur are sequentially added to an internal mixer for first-stage mixing for 7 minutes, and the rotation speed is controlled to discharge the rubber at 50°C to obtain a mixed rubber; the mixed rubber is then allowed to cool at room temperature, and the cooled rubber is placed in an internal mixer for second-stage mixing for 3 minutes, and the rotation speed is controlled to discharge the rubber at 160°C. After cooling, a vulcanization bag is added to an open mixer, and the sheet is removed after triangle bagging, and then allowed to stand overnight, and molded and vulcanized at 150°C according to the positive vulcanization time to obtain a sample. The corresponding formula and sample are shown in comparative sample 2, sample 4 and sample 5;

[0040] The preparation method of the ionic liquid copolymerized sulfur is as follows:

[0041] 5g of sulfur was melted at 130°C, 5g of 4-vinylbenzyl chloride was added, and the mixture was reacted at the same temperature for 6h to obtain a chlorine-containing copolymer. 2.5g of N-methylimidazole was added to quaternize the chlorine-containing copolymer to obtain an ionic liquid copolymer with the following structural formula:

[0042]

[0043] The tensile strength, elongation at break and 300% modulus of elongation were measured according to ISO37-2005, the test temperature was room temperature, and the tensile rate was 500 mm / min; the fatigue heat generation was measured according to ISO 4666-3:2016; and the rolling resistance (tanδ value at 60°C at 7% strain and 10 Hz frequency) was measured using RPA. The test characterization results of the samples are shown in Table 2.

[0044] In Table 1, SSBR is solution styrene butadiene rubber, model VSL5025-2, and the oil filling amount is 37.5phr; BR is butadiene rubber, model CB24; NR is natural rubber, model 3L; the amount of raw rubber in this embodiment is the sum of the oil-filled SSBR minus the oil part, BR and NR;

[0045] Table 1 Formulation and process

[0046]

[0047]

[0048] Anti-aging agent 4010NA 2 parts;

[0049] Vulcanization package: 3 parts zinc oxide, 2 parts stearic acid, 1.5 parts accelerator CZ, 2 parts accelerator D, 1.5 parts sulfur;

[0050] Table 2 Quasi-static mechanical properties and dynamic properties

[0051]

[0052] Combining the comparison sample 1 and samples 1 to 3, it can be seen that compared with the rubber composite material before modification, the tensile strength and 300% elongation stress (MPa) of the rubber composite material with the addition of ionic liquid copolymer sulfur are significantly improved, and the loss factor and fatigue temperature rise are significantly reduced. Among them, the tensile strength is increased by about 30%, the 300% elongation stress is increased by about 33%, the loss factor is reduced by about 35%, and the fatigue temperature rise is reduced by about 51%. It shows that the introduction of ionic liquid copolymer sulfur into the rubber composite material can effectively improve the quasi-static mechanical properties and dynamic fatigue properties of the rubber composite material. In addition, with the increase of the amount of ionic liquid copolymer sulfur added, the comprehensive performance of the rubber composite material is further enhanced. This may be due to the addition of ionic liquid copolymer sulfur, which can simultaneously enhance the silanization reaction of catalytic Si69 and white carbon black, and enhance the direct interface strength of rubber and white carbon black through polysulfide chains. The use efficiency of silane coupling agent and the dispersion of white carbon black in the rubber matrix are significantly improved, and the interface adhesion between materials is stronger.

[0053] Combining the comparative sample 2 and samples 4-5, it can be seen that when the amount of silane coupling agent is reduced, the performance of the rubber composite material with the addition of ionic liquid copolymerized sulfur is still better than that of the rubber composite material without the addition of ionic liquid copolymerized sulfur. This shows that the method of the present invention can reduce the amount of silane coupling agent while maintaining the comprehensive mechanical properties of the rubber composite material, has a higher modification efficiency, and is conducive to reducing VOC emissions.

[0054] According to the formula in Table 3, raw rubber, antioxidant, white carbon black, silane coupling agent and ionic liquid copolymer sulfur were added to the internal mixer in sequence for one-stage mixing for 10 minutes, and the speed was controlled to discharge the rubber at 70°C to obtain a mixed rubber; the mixed rubber was then placed at room temperature for cooling, and the cooled rubber was placed in the internal mixer for two-stage mixing for 3 minutes, and the speed was controlled to discharge the rubber at 170°C. After cooling, a vulcanization bag was added to the open mixer, and the triangle bag was made and the sheet was removed, and then placed overnight, and molded and vulcanized at 150°C according to the positive vulcanization time to obtain a sample; the corresponding formulas and samples are shown in comparative sample 3, sample 6, sample 7, sample 8, sample 9 and sample 10. The sample test characterization method is the same as the above method, and the results are shown in Table 4. Among them, when the cation is butyl imidazole and the anion is hexafluorophosphate, the preparation method of the ionic liquid copolymer sulfur includes: melting 5g of sulfur at 165°C, adding 5g of 1-vinyl-3-butyl imidazole bromide, reacting for 3h to obtain an ionic liquid with butyl imidazole as the cation and bromine as the anion, dissolving the ionic liquid in water, adding 3.2g of hexafluorophosphoric acid for anion replacement reaction, and obtaining an ionic liquid copolymer sulfur with butyl imidazole as the cation and hexafluorophosphate as the anion; the preparation methods of the remaining ionic liquid copolymer sulfurs are basically the same as the above method.

[0055] Table 3 Formulation and process

[0056]

[0057]

[0058] Anti-aging agent 4010NA 2 parts;

[0059] Vulcanization package: 3 parts zinc oxide, 2 parts stearic acid, 1.5 parts accelerator CZ, 2 parts accelerator D, 1.5 parts sulfur;

[0060] Table 4 Quasi-static mechanical properties and dynamic properties

[0061] Comparison sample 3 Sample 6 Sample 7 Sample 8 Sample 9 Sample 10 Tensile strength(MPa) 16.4 17.8 18.4 18.7 18.5 18.0 Elongation at break (%) 400 420 413 405 407 410 300% tensile stress (MPa) 14.6 16.8 17.5 18.3 18.0 17.8 Tanδ value (7%, 10Hz, 60℃) 0.211 0.162 0.145 0.130 0.132 0.140 Fatigue temperature rise(℃) 25.2 18.6 15.3 14.4 13.1 14.6

[0062] Combining the comparative sample 3 and samples 6 to 10, it can be seen that the rubber composite material added with the ionic liquid copolymerized sulfur of the present invention has significantly higher tensile strength, 300% tensile stress, and significantly lower loss factor and fatigue temperature rise than the rubber composite material added with the ionic liquid. This is because the small molecule ionic liquid has poor compatibility with the rubber matrix, and its plasticizing properties will reduce the modulus and fracture strength of the rubber composite material. The ionic liquid copolymerized sulfur can effectively improve the compatibility of the ionic liquid with the rubber, which is mainly attributed to its ability to be grafted on the molecular chain of the rubber.

[0063] Based on samples 6 to 8, it can be seen that when the cationic group in the ionic liquid copolymer sulfur remains unchanged, as the anionic group changes from tetrafluoroborate (sample 6) and hexafluorophosphate (sample 7) to acetate (sample 8), the tensile strength and rolling resistance properties of the rubber composite material show an improving trend. According to samples 8 to 10, when the anionic group in the ionic liquid copolymer sulfur remains unchanged, and the cationic group changes from triphenylphosphine (sample 10) and pyridine (sample 9) to imidazole (sample 8), the rolling resistance performance of the composite material shows an increasing trend, indicating that as the alkalinity of the ionic liquid copolymer sulfur increases, the comprehensive performance of the rubber composite material improves, which may be because the alkaline ionic liquid copolymer sulfur is more efficient in promoting the silanization reaction.

Claims

1. A rubber composite material, characterized in that: The raw materials include raw rubber, white carbon black, ionic liquid copolymer sulfur, silane coupling agent, antioxidant and vulcanization package; the weight of white carbon black is 50wt% to 100wt% of the raw rubber, the weight of ionic liquid copolymer sulfur is 0.1wt% to 3wt% of the white carbon black, and the weight of silane coupling agent / white carbon black is ≤10wt%.

2. The rubber composite material according to claim 1, characterized in that: The weight of the silane coupling agent is 4wt% to 10wt% of the white carbon black.

3. The rubber composite material according to claim 1, characterized in that: The silane coupling agent is sulfur-containing alkoxysilane.

4. The rubber composite material according to claim 1, characterized in that: In the ionic liquid of the ionic liquid copolymer sulfur, the cation part is alkyl imidazole, alkyl pyridine or organic phosphonium salt, and the anion part is chlorine, bromine, iodine, hexafluorophosphate, tetrafluoroborate, acetate or hydroxide.

5. The rubber composite material according to claim 4, characterized in that: The cationic part is alkyl imidazole, and the anionic part is hydroxide, acetate or chloride.

6. The rubber composite material according to claim 1, characterized in that: The raw rubber is diene rubber.

7. A method for preparing the rubber composite material according to claim 1, characterized in that: include: Adding raw rubber, antioxidant, white carbon black, silane coupling agent and ionic liquid copolymerized sulfur into an internal mixer in sequence and mixing them to obtain a first-stage mixed rubber; The first-stage rubber mix is ​​cooled and then mixed in an internal mixer to obtain a second-stage rubber mix; The second-stage mixed rubber is cooled and then mixed with a vulcanizing bag and vulcanized to obtain a rubber composite material.

8. The method according to claim 7, characterized in that In the first stage of mixing, the rotor speed is 20-40 rpm, the mixing time is 3-10 minutes, and the discharge temperature is 50-70°C.

9. The method according to claim 7, characterized in that: In the second stage mixing, the rotor speed is 30-70 rpm, the mixing time is 2-6 minutes, and the debonding temperature is 130-170°C.

Citation Information

Patent Citations

  • Method for preparing high-performance tread rubber by use of silanization reaction of ionic liquid in-situ catalytic filler

    CN104804231A

  • Methods for modifying silica with aliphatic polyoxyethylene ether and its compounding with rubber

    CN106832417B

  • A method for preparing chemically coated hydrophobic silica

    CN110734653B

  • Ionic liquid modified carbon black-white carbon black double-phase particle filling natural rubber and preparation method thereof

    CN103275365A

  • Preparation method of sulfur-containing silane copolymer modified white carbon black-rubber composite material

    CN113980366A